Current status of Neisseria gonorrhoeae cervicitis in pregnant women in Japan. - Shunji Suzuki; Shin-Ichi Hoshi; Akihiko Sekizawa; Yoko Sagara; Masanobu Tanaka; Katsuyuki Kinoshita; Tadaichi Kitamura (PLoS ONE, 2019)
We evaluated the current prevalence of gonococcal cervicitis among pregnant women in institutes that either do or do not routinely screen for gonococcal infection in Japan. We requested 2,330 obstetrical facilities to provide information on Neisseria gonorrhoeae cervicitis in pregnant women. A total of 1,876 (80.5%) of them responded. The universal screening test for gonococcal cervicitis, involving nucleic acid amplification for all pregnant women, was performed in 281 institutes (13.9% of institutes across Japan). The total rate of pregnant women with gonococcal cervicitis was 1.3% in the institutes performing the screening test during pregnancy, while it was only 0.2% (p < 0.01) in those not performing it. This suggests that 84% of infected women may have been missed in the institutes that do not routinely perform the screening test for gonococcal cervicitis. It may be time to examine the cost-effectiveness of providing gonococcal screening for all pregnant women in Japan.